High-temperature-resistant anticorrosive coated fracturing quartz sand and preparation method thereof

CN122959015APending Publication Date: 2026-10-23PANJIN XINGLONGTAI DISTRICT GAOXIN IND CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611125573.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,传统邻苯二甲腈树脂需要280℃以上的高温才能发生氰基环化聚合反应,远超压裂支撑剂覆膜工艺的常规温度窗口,且树脂本征脆性极大、与石英砂表面附着力差,因而本领域技术人员从未将其作为覆膜材料候选用于压裂支撑剂的改性

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The application discloses a kind of high-temperature-resistant anticorrosion film-coated fracturing quartz sand and preparation method, belong to the technical field of proppant for oil and gas well.The film-coated fracturing quartz sand includes quartz sand base body and the modified phthalonitrile resin film layer coated on its surface;Wherein modified phthalonitrile resin is prepared by grafting polydimethylsiloxane flexible segment and 3-glycidyl ether oxypropyl trimethoxysilane on phthalonitrile molecular main chain in the form of covalent bond.The application improves the high-temperature resistance, corrosion resistance, interfacial bonding strength and long-term service stability of the film layer by PDMS flexible segment toughening and KH560 pre-hydrolysis forming chemical bond with quartz sand, maintains extremely low breakage rate and excellent flow conductivity retention rate in harsh environments such as high temperature and acidity, alkalinity, high salt and crude oil, and has unique high-temperature self-reinforcing effect, especially suitable for fracturing construction of deep and ultra-deep oil and gas wells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of proppant technology for oil and gas wells, and in particular to a high-temperature resistant, corrosion-resistant, coated fracturing quartz sand and its preparation method. Background Technology

[0002] Hydraulic fracturing is a core technology for enhancing the production of low-permeability oil and gas reservoirs. As a key material in fracturing operations, proppant performance directly determines the conductivity of fractures and the long-term production of oil and gas wells. Among various proppants, quartz sand holds a major share of the global proppant market due to its wide availability, low cost, and moderate density. However, natural quartz sand itself has low compressive strength, and numerous microcracks are generated on its surface during mining, crushing, and screening. This makes it prone to breakage under downhole closure pressure, and the resulting fine powder can clog fracture channels, severely reducing conductivity. Furthermore, as oil and gas exploration and development continue to extend into deeper and ultra-deep formations, with formation temperatures exceeding 200℃, closure pressures exceeding 70MPa, and the presence of acidic gases such as H2S and CO2, traditional quartz sand can no longer meet such demanding service environments.

[0003] To improve the performance of quartz sand, existing technologies generally employ resin coating for surface modification. Early methods used thermosetting resins such as phenolic resin, epoxy resin, and furan resin to coat the quartz sand, forming a protective layer through resin curing and cross-linking, which improved the compressive strength and corrosion resistance of the proppant to some extent. Subsequently, to meet the demands of higher temperatures, those skilled in the art developed high-performance coating materials such as organosilicon-modified resins and polyimide resins, and designed multi-layered coating structures to balance strength and toughness. However, these technical solutions still have insurmountable drawbacks. First, most organic resin coatings undergo thermal softening, thermal oxidative degradation, or main chain breakage under long-term high-temperature environments, leading to coating failure, proppant particle adhesion, a sharp decrease in porosity, and a significant reduction in conductivity. Second, the interfacial bonding between existing coating resins and quartz sand mainly relies on physical adsorption and single-layer chemical bonds formed by a small amount of silane coupling agent, resulting in limited bonding strength. Under high temperature, high pressure, and fluid erosion, the coating layer is easily peeled off, losing its protective function for the quartz sand. Furthermore, traditional resin molecular chains contain numerous easily hydrolyzed groups such as ester bonds, ether bonds, or amide bonds. Prolonged immersion in acidic media can lead to hydrolytic degradation and insufficient corrosion resistance. Increasing the thickness of the coating layer to improve corrosion resistance, however, increases the proppant density, reduces pumpability, and significantly increases production costs.

[0004] Phthalonil resin is a high-performance thermosetting resin with cyano groups as crosslinking end groups. After curing, it forms a highly conjugated aromatic heterocyclic three-dimensional network dominated by triazine, isoindoline, and phthalocyanine rings, exhibiting extremely high thermal stability, excellent chemical inertness, and low water absorption. It has been widely used in aerospace, electronic packaging, and other fields. However, traditional phthallonil resin requires temperatures above 280°C to undergo cyano cyclization polymerization, far exceeding the conventional temperature window for fracturing proppant coating processes. Furthermore, the resin is inherently extremely brittle and has poor adhesion to quartz sand surfaces. Therefore, those skilled in the art have never considered it as a candidate coating material for modifying fracturing proppants. Although some studies have attempted to lower the curing temperature by adding amino curing agents, heterogeneous catalysis leads to uneven distribution of the curing agent, incomplete local curing, and residual curing agent becoming internal defects in the resin, potentially causing the release of toxic and harmful substances. Therefore, how to reduce the curing temperature, improve the toughness and interfacial bonding of phthalonitrile resin while maintaining its excellent high temperature resistance and corrosion resistance, and successfully apply it to the coating of fracturing quartz sand, has been a long-standing technical problem in this field. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a high-temperature resistant and corrosion-resistant coated fracturing quartz sand and its preparation method.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: a high-temperature resistant and corrosion-resistant coated fracturing quartz sand, comprising the following components by weight: quartz sand: 90-100 parts, modified phthalonitrile resin: 3-10 parts.

[0007] Preferably, the modified phthalonitrile resin is prepared as follows: (1) Under nitrogen protection, hydroxyl-terminated polydimethylsiloxane was added to N,N-dimethylformamide and stirred for 20-30 min. Potassium hydroxide was added, the temperature was raised to 80-85℃, and the reaction was maintained for 3-5 h. Then the temperature was cooled to 30-40℃, 4-amino-5-nitrophthalonitrile was added, the temperature was raised to 85-95℃, and the reaction was maintained for 6-9 h. After the reaction was completed, the temperature was cooled to room temperature, toluene was added, and the mixture was stirred for 10-20 min. Then the mixture was poured into dilute hydrochloric acid solution to precipitate the precipitate. The precipitate was filtered, and the filter cake was washed once with deionized water and once with ethanol. After drying, phthalonitrile containing flexible silane segments was obtained. The chemical reaction is shown in the diagram below: (2) Under nitrogen protection, phthalonitrile containing flexible silane segments was added to anhydrous 1,4-dioxane, heated to 30-40℃, and stirred until dissolved. Then, 3-glycidyl etheroxypropyltrimethoxysilane was added, heated to 40-60℃, and stirred for 1-3 hours. After the reaction was completed, the reaction solution was poured into 3-10 times the volume of n-hexane to precipitate. The supernatant was poured off, and the precipitate was washed with n-hexane 3-4 times. After drying, the modified phthalonitrile resin was obtained. The chemical reaction is shown in the following diagram: Preferably, the number average molecular weight of the hydroxyl-terminated polydimethylsiloxane in (1) is 1500-2000.

[0008] Preferably, in (1), the molar ratio of hydroxyl-terminated polydimethylsiloxane, potassium hydroxide and 4-amino-5-nitrophthalonitrile is 1:2.5-4:2.

[0009] Preferably, in (1), the hydroxyl-terminated polydimethylsiloxane, N,N-dimethylformamide, toluene and dilute hydrochloric acid solution are in a weight ratio of 1:2-3:0.5-1:10-20.

[0010] Preferably, the concentration of the dilute hydrochloric acid solution in (1) is 3-10 wt%.

[0011] Preferably, in (2), the phthalonitrile containing flexible silane segments and 3-glycidoxypropyltrimethoxysilane are in a molar ratio of 1:2-2.2.

[0012] Preferably, in (2), the ratio of phthalonitrile containing flexible silane segments and anhydrous 1,4-dioxane is 1:5-10 by weight.

[0013] Furthermore, the present invention also provides a method for preparing high-temperature resistant and corrosion-resistant coated fracturing quartz sand, comprising the following steps: S1. Add the modified phthalonitrile resin to acetone, stir until completely dissolved, add deionized water, adjust the pH to 4.5-5.0 with glacial acetic acid, stir evenly, and let stand at room temperature for 40-50 minutes to obtain a pre-hydrolyzed modified phthalonitrile resin solution. S2. Wash the quartz sand with deionized water until the conductivity is <10μS / cm, and dry it to obtain pretreated quartz sand; S3. Add the pretreated quartz sand to the coating machine, and spray the pre-hydrolyzed modified phthalonitrile resin solution through atomization in 8-12 minutes while stirring. After spraying, continue stirring for 10-20 minutes. Then, while stirring, raise the temperature to 75-85℃ and hold for 15-25 minutes, and then raise the temperature to 115-125℃ and hold for 25-35 minutes to complete the pre-condensation. S4. After pre-condensation, heat the sand to 180-190℃ at a rate of 2-5℃ / min and hold for 1 hour. Then heat the sand to 210-220℃ and hold for 1 hour. Finally, heat the sand to 240-260℃ and hold for 2 hours to obtain high-temperature resistant and corrosion-resistant coated fracturing quartz sand.

[0014] Preferably, the modified phthalonitrile resin, acetone and deionized water in S1 are in a weight ratio of 1:3-6:0.1-0.2.

[0015] Preferably, the mechanism of action of the high-temperature resistant and corrosion-resistant coated fracturing quartz sand in this invention is explained as follows: The high-temperature corrosion resistant coated fracturing quartz sand of the present invention grafts flexible segments of polydimethylsiloxane (PDMS) and KH560 silane coupling agent into the molecular structure of phthalonitrile (PN) in the form of chemical covalent bonds. Through pre-hydrolysis and gradient curing coating process, the coating layer forms a strong Si-O-Si covalent bond with the quartz sand matrix.

[0016] Traditional phthalonitrile resins have weak electrophilic cyano groups, requiring temperatures above 280°C to provide sufficient activation energy for cyclization polymerization, which far exceeds the conventional temperature window for proppant coating processes. This is the fundamental reason why those skilled in the art have never included them in the candidate range of coating materials.

[0017] Existing modification technologies often employ heterogeneous catalysis with added amino curing agents. This not only results in low catalytic efficiency but also leads to incomplete curing due to uneven curing agent distribution, and residual free curing agents can become defects within the resin. This invention innovatively bonds secondary amino and secondary hydroxyl groups directly to the resin molecular backbone, forming a homogeneous synergistic catalytic system: the secondary amino group acts as the main catalyst, its lone pair electrons attacking the electron-deficient carbon atom of the cyano group to form a negatively charged amidine intermediate, thereby initiating a chain polymerization reaction; the secondary hydroxyl group acts as a co-catalyst, activating the cyano group through hydrogen bonding and simultaneously providing protons in key steps of the cyclization reaction, promoting the stability and transformation of the intermediate. This homogeneous synergistic catalysis significantly lowers the initial curing temperature of the resin and eliminates the need for any external curing agents, avoiding the release of pores and toxic substances from the coating layer caused by curing agent volatilization.

[0018] The three-dimensional aromatic heterocyclic network formed by cyano addition polymerization is the structural basis for high-temperature resistance. Unlike traditional coating materials such as phenolic resins and epoxy resins, which release small molecule byproducts during curing, PN resin forms a cross-linked aromatic heterocyclic structure dominated by triazine rings, isoindoline rings, and phthalocyanine rings through nucleophilic addition cyclization polymerization. No small molecules are released during curing, resulting in a dense, non-porous coating layer. These aromatic heterocycles possess a highly conjugated aromatic system, with the bond energies of C≡N and CN bonds within the rings far exceeding those of C≡C bonds. Strong π-π stacking interactions between molecules form a dense three-dimensional network. The glass transition temperature of PN resin after curing can reach over 400℃.

[0019] Meanwhile, the introduction of PDMS segments did not sacrifice thermal stability. The Si-O-Si main chain bond energy of PDMS is much higher than that of C-C bonds, and its introduction into the PN network improves toughness without significantly reducing the heat resistance of the resin bulk.

[0020] The corrosion resistance of the coating layer comes from the triple synergy of the chemical inertness of the PN aromatic heterocyclic network, the low surface energy hydrophobicity of the PDMS segments, and the defect-free interface barrier constructed by the covalent bonding of silanol groups.

[0021] The PN aromatic heterocyclic network endows the coating layer with excellent chemical inertness. One of the important reasons for the failure of traditional organic resin coating layers is that the molecular chain contains a large number of easily hydrolyzed ester bonds, ether bonds, or amide bonds. Acidic media (acidic solutions formed by H2S and CO2 dissolved in formation water) can easily penetrate through these polar groups and catalyze the degradation of the network. The highly conjugated aromatic heterocyclic structure formed after PN curing contains almost no easily hydrolyzed chemical bonds. The carbon-nitrogen bonds are extremely stable under weakly acidic conditions and do not have the electronic structure to undergo acid-catalyzed hydrolysis. The Si-O-Si backbone of PDMS has extremely low surface energy and good hydrophobicity. This characteristic forms a natural hydrophobic barrier on the outer surface and near-surface region of the coating layer, making it difficult for water molecules and acid radicals to effectively wet and adhere, and greatly limiting the penetration depth of acidic media. The core interface design of this invention involves grafting KH560 onto the side chains of PN resin via chemical covalent bonds. Its trimethoxysilyl groups hydrolyze under weakly acidic conditions to generate silanol groups, which then undergo a condensation reaction with the silanol groups on the quartz sand surface during the coating process, forming a continuous Si-O-Si chemical bond network across the interface. This design eliminates macroscopic interfacial gaps between the coating layer and the quartz sand matrix, depriving acidic media of a pathway for side penetration.

[0022] The most outstanding counterintuitive technical effect of this invention is that the breakage rate of coated sand does not increase after long-term aging at 250°C.

[0023] The fundamental reason for this phenomenon lies in the unique incomplete conversion and gradual improvement mechanism of PN resin. During the coating molding stage, the cyclization polymerization reaction of the cyano group is not completely converted, and the coating layer retains a high degree of molecular chain mobility and some unreacted functional groups. When the support agent enters S1, the modified phthalonitrile resin is added to acetone and stirred until completely dissolved. Deionized water is added, and the pH is adjusted to 4.5-5.0 with glacial acetic acid. After stirring evenly, it is allowed to stand at room temperature for 40-50 minutes to obtain a pre-hydrolyzed modified phthalonitrile resin solution. S2. Wash the quartz sand with deionized water until the conductivity is <10μS / cm, and dry it to obtain pretreated quartz sand; S3. Add the pretreated quartz sand to the coating machine, and spray the pre-hydrolyzed modified phthalonitrile resin solution through atomization in 8-12 minutes while stirring. After spraying, continue stirring for 10-20 minutes. Then, while stirring, raise the temperature to 75-85℃ and hold for 15-25 minutes, and then raise the temperature to 115-125℃ and hold for 25-35 minutes to complete the pre-condensation. S4. After pre-condensation, heat the sand to 180-190℃ at a rate of 2-5℃ / min and hold for 1 hour. Then heat the sand to 210-220℃ and hold for 1 hour. Finally, heat the sand to 240-260℃ and hold for 2 hours to obtain high-temperature resistant and corrosion-resistant coated fracturing quartz sand.

[0024] Preferably, the modified phthalonitrile resin, acetone and deionized water in S1 are in a weight ratio of 1:3-6:0.1-0.2.

[0025] Preferably, the mechanism of action of the high-temperature resistant and corrosion-resistant coated fracturing quartz sand in this invention is explained as follows: The high-temperature corrosion resistant coated fracturing quartz sand of the present invention grafts flexible segments of polydimethylsiloxane (PDMS) and KH560 silane coupling agent into the molecular structure of phthalonitrile (PN) in the form of chemical covalent bonds. Through pre-hydrolysis and gradient curing coating process, the coating layer forms a strong Si-O-Si covalent bond with the quartz sand matrix.

[0026] Traditional phthalonitrile resins have weak electrophilic cyano groups, requiring temperatures above 280°C to provide sufficient activation energy for cyclization polymerization, which far exceeds the conventional temperature window for proppant coating processes. This is the fundamental reason why those skilled in the art have never included them in the candidate range of coating materials.

[0027] Existing modification technologies often employ heterogeneous catalysis with added amino curing agents. This not only results in low catalytic efficiency but also leads to incomplete curing due to uneven curing agent distribution, and residual free curing agents can become defects within the resin. This invention innovatively bonds secondary amino and secondary hydroxyl groups directly to the resin molecular backbone, forming a homogeneous synergistic catalytic system: the secondary amino group acts as the main catalyst, its lone pair electrons attacking the electron-deficient carbon atom of the cyano group to form a negatively charged amidine intermediate, thereby initiating a chain polymerization reaction; the secondary hydroxyl group acts as a co-catalyst, activating the cyano group through hydrogen bonding and simultaneously providing protons in key steps of the cyclization reaction, promoting the stability and transformation of the intermediate. This homogeneous synergistic catalysis significantly lowers the initial curing temperature of the resin and eliminates the need for any external curing agents, avoiding the release of pores and toxic substances from the coating layer caused by curing agent volatilization.

[0028] The three-dimensional aromatic heterocyclic network formed by cyano addition polymerization is the structural basis for high-temperature resistance. Unlike traditional coating materials such as phenolic resins and epoxy resins, which release small molecule byproducts during curing, PN resin forms a cross-linked aromatic heterocyclic structure dominated by triazine rings, isoindoline rings, and phthalocyanine rings through nucleophilic addition cyclization polymerization. No small molecules are released during curing, resulting in a dense, non-porous coating layer. These aromatic heterocycles possess a highly conjugated aromatic system, with the bond energies of C≡N and CN bonds within the rings far exceeding those of C≡C bonds. Strong π-π stacking interactions between molecules form a dense three-dimensional network. The glass transition temperature of PN resin after curing can reach over 400℃.

[0029] Meanwhile, the introduction of PDMS segments did not sacrifice thermal stability. The Si-O-Si main chain bond energy of PDMS is much higher than that of C-C bonds, and its introduction into the PN network improves toughness without significantly reducing the heat resistance of the resin bulk.

[0030] The corrosion resistance of the coating layer comes from the triple synergy of the chemical inertness of the PN aromatic heterocyclic network, the low surface energy hydrophobicity of the PDMS segments, and the defect-free interface barrier constructed by the covalent bonding of silanol groups.

[0031] The PN aromatic heterocyclic network endows the coating layer with excellent chemical inertness. One of the important reasons for the failure of traditional organic resin coating layers is that the molecular chain contains a large number of easily hydrolyzed ester bonds, ether bonds, or amide bonds. Acidic media (acidic solutions formed by H2S and CO2 dissolved in formation water) can easily penetrate through these polar groups and catalyze the degradation of the network. The highly conjugated aromatic heterocyclic structure formed after PN curing contains almost no easily hydrolyzed chemical bonds. The carbon-nitrogen bonds are extremely stable under weakly acidic conditions and do not have the electronic structure to undergo acid-catalyzed hydrolysis. The Si-O-Si backbone of PDMS has extremely low surface energy and good hydrophobicity. This characteristic forms a natural hydrophobic barrier on the outer surface and near-surface region of the coating layer, making it difficult for water molecules and acid radicals to effectively wet and adhere, and greatly limiting the penetration depth of acidic media. The core interface design of this invention involves grafting KH560 onto the side chains of PN resin via chemical covalent bonds. Its trimethoxysilyl groups hydrolyze under weakly acidic conditions to generate silanol groups, which then undergo a condensation reaction with the silanol groups on the quartz sand surface during the coating process, forming a continuous Si-O-Si chemical bond network across the interface. This design eliminates macroscopic interfacial gaps between the coating layer and the quartz sand matrix, depriving acidic media of a pathway for side penetration.

[0032] The most outstanding counterintuitive technical effect of this invention is that the breakage rate of coated sand does not increase after long-term aging at 250°C.

[0033] The fundamental reason for this phenomenon lies in the unique incomplete conversion and gradual improvement mechanism of PN resin. During the coating molding stage, the cyclization polymerization reaction of the cyano group did not achieve complete conversion, and the coating layer retained high molecular chain mobility and some unreacted functional groups. When the proppant (with an average molecular weight of 2000) was added to 600g of N,N-dimethylformamide, stirred for 30min, 0.4mol of potassium hydroxide was added, the temperature was raised to 85℃, and the reaction was maintained for 5h. Then, it was cooled to 40℃, 0.2mol of 4-amino-5-nitrophthalonitrile was added, the temperature was raised to 95℃, and the reaction was maintained for 9h. After the reaction was completed, it was cooled to room temperature, 200g of toluene was added, stirred for 20min, and then poured into 4kg of 10wt% dilute hydrochloric acid solution to precipitate. After filtration, the filter cake was washed once with deionized water and once with ethanol. After drying, phthalonitrile containing flexible silane segments was obtained. (2) Under nitrogen protection, 228 g (0.1 mol) of phthalonitrile containing flexible silane segments was added to 2.28 kg of anhydrous 1,4-dioxane, heated to 40 °C, and stirred until dissolved. Then 0.22 mol of 3-glycidyl etheroxypropyltrimethoxysilane was added, heated to 60 °C, and stirred for 1 h. After the reaction was completed, the reaction solution was poured into 10 times the volume of n-hexane to precipitate. The supernatant was poured off, and the precipitate was washed 4 times with n-hexane and dried to obtain modified phthalonitrile resin.

[0034] Comparative Preparation Example 1: The difference between Comparative Preparation Example 1 and Preparation Example 2 is that step (2) is omitted, and the product obtained after the reaction according to step (1) is denoted as modified phthalonitrile resin.

[0035] Comparative Preparation Example 2: The difference between Comparative Preparation Example 2 and Preparation Example 2 is that the hydroxyl-terminated polydimethylsiloxane is replaced with dimethylsilanedimethyldiethanol, the chemical structure of which is as follows: Example 1: A specific preparation method of high-temperature resistant and corrosion-resistant coated fracturing quartz sand, comprising the following steps: S1. Add 30g of the modified phthalonitrile resin prepared according to Preparation Example 1 to 90g of acetone, stir until completely dissolved, add 3g of deionized water, adjust the pH to 4.5 with glacial acetic acid, stir evenly, and let stand at room temperature for 40min to obtain a pre-hydrolyzed modified phthalonitrile resin solution. S2. Wash 900g of quartz sand with deionized water until the conductivity is <10μS / cm, and dry it to obtain pretreated quartz sand; S3. Add the pretreated quartz sand to the coating machine, and spray the pre-hydrolyzed modified phthalonitrile resin solution with atomization for 8 minutes while stirring. After spraying, continue stirring for 10 minutes. Then, keep stirring and heat up to 75°C for 15 minutes, and then heat up to 115°C for 25 minutes to complete the pre-condensation. S4. After pre-condensation, the temperature is increased to 180℃ at a rate of 2℃ / min and held for 1 hour, then increased to 210℃ and held for 1 hour, and finally increased to 240℃ and held for 2 hours to obtain high-temperature resistant and corrosion-resistant coated fracturing quartz sand.

[0036] Example 2: A specific preparation method of high-temperature resistant and corrosion-resistant coated fracturing quartz sand, comprising the following steps: S1. Add 50g of the modified phthalonitrile resin prepared according to Preparation Example 2 to 250g of acetone, stir until completely dissolved, add 7.5g of deionized water, adjust the pH to 4.7 with glacial acetic acid, stir evenly, and let stand at room temperature for 45min to obtain a pre-hydrolyzed modified phthalonitrile resin solution. S2. Wash 950g of quartz sand with deionized water until the conductivity is <10μS / cm, and dry it to obtain pretreated quartz sand; S3. Add the pretreated quartz sand to the coating machine, and spray the pre-hydrolyzed modified phthalonitrile resin solution with atomization in 10 minutes while stirring. After spraying, continue stirring for 15 minutes. Then, keep stirring and heat up to 80°C for 20 minutes, and then heat up to 120°C for 30 minutes to complete the pre-condensation. S4. After pre-condensation, the temperature is increased to 185℃ at a rate of 3℃ / min and held for 1 hour, then increased to 215℃ and held for 1 hour, and finally increased to 250℃ and held for 2 hours to obtain high-temperature resistant and corrosion-resistant coated fracturing quartz sand.

[0037] Example 3: A specific preparation method for high-temperature resistant and corrosion-resistant coated fracturing quartz sand, comprising the following steps: S1. Add 100g of the modified phthalonitrile resin prepared according to Preparation Example 3 to 600g of acetone, stir until completely dissolved, add 20g of deionized water, adjust the pH to 5.0 with glacial acetic acid, stir evenly, and let stand at room temperature for 50min to obtain a pre-hydrolyzed modified phthalonitrile resin solution. S2. Wash 1 kg of quartz sand with deionized water until the conductivity is <10 μS / cm, and dry it to obtain pretreated quartz sand; S3. Add the pretreated quartz sand to the coating machine, and spray the pre-hydrolyzed modified phthalonitrile resin solution in 12 minutes with stirring. After spraying, continue stirring for 20 minutes. Then, keep stirring and raise the temperature to 85°C and hold for 25 minutes. Then raise the temperature to 125°C and hold for 35 minutes to complete the pre-condensation. S4. After pre-condensation, the temperature is increased to 190℃ at a rate of 5℃ / min and held for 1 hour, then increased to 220℃ and held for 1 hour, and finally increased to 260℃ and held for 2 hours to obtain high-temperature resistant and corrosion-resistant coated fracturing quartz sand.

[0038] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that Comparative Example 1 uses traditional phenolic resin coated sand. Preparation method: 950g of quartz sand was washed with deionized water until the conductivity was <10μS / cm, dried at 150℃ for 3 hours, cooled to 60℃ and added to a coating machine, along with 50g of ordinary thermosetting phenolic resin and 2.5g of hexamethylenetetramine curing agent. The mixture was stirred for 8 minutes, heated to 120℃ and held for 30 minutes, and then cured according to the curing regime of Example 2: 185℃ / 1h → 215℃ / 1h → 250℃ / 2h. The finished product was obtained after cooling.

[0039] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the modified phthalonitrile resin prepared according to Preparation Example 2 was replaced with commercially available bisphenol A type phthalonitrile resin, and 4 wt% of 4,4'-diaminodiphenylmethane was added as an external curing agent. The coating process of Example 2 was followed, and the curing regime was adjusted to the standard process: 200℃ / 1h → 230℃ / 1h → 280℃ / 2h → 320℃ / 2h.

[0040] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the modified phthalonitrile resin prepared according to Preparation Example 2 is replaced with the modified phthalonitrile resin prepared according to Comparative Preparation Example 1.

[0041] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the modified phthalonitrile resin prepared according to Preparation Example 2 is replaced with the modified phthalonitrile resin prepared according to Comparative Preparation Example 2.

[0042] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that the modified phthalonitrile resin prepared in Example 2 of this invention is used, but instead of solvent coating, the traditional melt method is used: 950g of quartz sand is heated to 185°C, 50g of resin is added, stirred and mixed for 10min, and then cured according to the curing regime of Example 2.

[0043] Performance testing: 1. Breakage rate test before and after high-temperature aging: The test was conducted according to the breakage rate test method of API RP 19C:2008 (first edition), with three temperature gradients: The first group was the room temperature control group, in which dried fracturing quartz sand samples were directly taken, and a closing pressure of 52 MPa was applied in the standard test device. After holding the pressure for 2 min, the pressure was released, the mass of the broken fine powder was sieved and weighed, and the breakage rate at room temperature was calculated; The second group was the 260℃ long-term aging group, in which the samples were placed in a high-temperature and high-pressure reactor, nitrogen was introduced to remove air, and the reactor was sealed. The temperature was increased to 260℃ at a rate of 2℃ / min, held for 72 h, and then naturally cooled to room temperature. The breakage rate at 52 MPa was tested using the same method; The third group was the 300℃ short-term aging group, in which the breakage rate was tested after holding the samples at 300℃ in a nitrogen atmosphere for 24 h. 2. Comprehensive corrosion resistance performance test: Acidic environment corrosion test To simulate an acidic formation water environment containing H2S and CO2, two gradients, one at medium temperature and one at high temperature, were set up. Precisely weighed proppant samples were soaked in a 15wt% hydrochloric acid solution at a liquid-to-solid ratio of 10:1. After sealing, the samples were placed in a constant temperature water bath and a high-temperature and high-pressure reactor, and kept at 80℃ and 180℃ for 72 hours, respectively. After removal, the samples were rinsed with deionized water until neutral and dried to constant weight. The breakage rate under a 52MPa closure pressure was then tested. Alkaline environment corrosion test To simulate alkaline fracturing fluid residue and high alkalinity formation water environment, a 10wt% sodium hydroxide solution was used as the corrosive medium. The sample was immersed in the solution at a liquid-to-solid ratio of 10:1, sealed, and kept at 80℃ and 180℃ for 72h respectively. After being taken out, the sample was repeatedly rinsed with deionized water until the pH of the filtrate was neutral. After drying, the breakage rate was tested. High-salt environment corrosion test To simulate the corrosive effects of highly mineralized formation water, a composite salt solution was used for testing: simulated formation water containing 15wt% sodium chloride and 5wt% calcium chloride was prepared, and the sample was soaked at a liquid-to-solid ratio of 10:1. The sample was then kept at 80℃ and 180℃ for 72 hours, respectively. After being removed, the sample was rinsed with deionized water to remove surface salts, dried, and the breakage rate was tested. Crude oil environmental corrosion test To simulate the swelling and erosion of the coating layer caused by long-term immersion in crude oil in the well, No. 0 diesel oil and crude oil were mixed at a ratio of 1:1 as the medium. The sample was immersed in crude oil at a liquid-solid ratio of 5:1 and sealed and kept at 120℃ and 260℃ for 72 hours respectively. After being taken out, the sample was ultrasonically cleaned three times with petroleum ether to remove the crude oil adsorbed on the surface. After drying to constant weight, the breakage rate was tested. 3. Coating layer interface bonding performance test: The roller wear method was used. 500g of dry fracturing quartz sand sample and 500g of standard bearing steel ball with a diameter of 5mm were added to a roller wear tester with a volume of 5L. After sealing, the roller was continuously rotated at a speed of 60r / min for 2h. After stopping, the sample was taken out and sieved with a 40-mesh standard sieve to remove fine powder and resin debris generated by wear. The mass of the remaining intact particles was weighed and the wear mass loss rate was calculated. 4. High-Temperature Particle Cohesion Test: Take 100g of dry fracturing quartz sand sample and spread it evenly in a cylindrical stainless steel mold with a diameter of 50mm. Place a stainless steel indenter above the sample and apply an axial pressure of 2MPa to simulate the compaction state of the proppant filling layer. Place the entire mold in a high-temperature oven and slowly heat it to 260℃ at a rate of 2℃ / min. After holding at this temperature for 4 hours, turn off the oven and allow it to cool naturally to room temperature. Remove the proppant blocks from the mold, gently disperse them by hand, and sieve them through a 20-mesh standard sieve. Weigh the mass of the remaining clumps on the sieve and calculate the particle cohesion rate (cohesion rate = mass of clumps / total sample mass × 100%). 5. Long-term conductivity retention test: The test was conducted according to API RP 19D:2021 standard, using a linear conductivity meter, with fracturing quartz sand at a rate of 5 kg / m³. 2 The standard sand concentration was evenly spread between two simulated formation rock slabs, assembled into a flow-conducting chamber, and a closing pressure of 52 MPa was applied. At the same time, the temperature was raised to 260°C, and simulated formation water with a total salinity of 20,000 mg / L was introduced. After the pressure and temperature stabilized, the initial flow capacity was tested. Then, it was continuously operated under these conditions for 72 hours, during which the closing pressure and temperature were kept constant, and the flow capacity was tested again. The long-term flow capacity retention rate was calculated (retention rate = flow capacity after 72 hours / initial flow capacity × 100%). The experimental results are shown in Table 1.

[0044] Table 1 Performance Test Results

[0045] Data Analysis: As can be seen from the performance test data in Table 1, the high-temperature resistant and corrosion-resistant coated fracturing quartz sand prepared by the technical solution of the present invention in Examples 1-3 is superior to the existing technology and the comparative sample in terms of high temperature resistance, corrosion resistance under all working conditions, interfacial bonding strength, high temperature anti-adhesion and long-term flow stability. Among them, Example 2 has the best comprehensive performance.

[0046] In terms of breakage rate and high-temperature resistance, Example 2 exhibited the best room-temperature mechanical properties and high-temperature stability, and even its mechanical properties improved further after long-term high-temperature aging. This is because the hydroxyl-terminated polydimethylsiloxane used in Example 2 achieved a balance between toughening effect and thermal stability; at the same time, the secondary amino and secondary hydroxyl groups that may be present in the molecule act as dual autocatalytic sites, resulting in high curing degree and a dense, defect-free coating layer; more importantly, the residual trace cyano groups undergo supplementary crosslinking during high-temperature aging, producing a unique downhole self-reinforcing effect. In contrast, the traditional phenolic resin used in Comparative Example 1 experienced rapid main chain breakage at high temperatures, resulting in a precipitous decline in performance; the unmodified phthalonitrile resin in Comparative Example 2 was extremely brittle, and the coating layer was prone to cracking; Comparative Example 3 did not have a grafted silane coupling agent, resulting in weak interfacial bonding and easy peeling of the coating; Comparative Example 4 used short-chain silanes, which had no toughening effect; and Comparative Example 5 used a melt coating method, where the silanes were not fully hydrolyzed, resulting in weak interfacial bonding.

[0047] In terms of corrosion resistance under all operating conditions, Example 2 exhibited the lowest performance degradation in various media, including acidic, alkaline, high-salt, and crude oil. This is attributed to the highly conjugated aromatic heterocyclic network formed by the curing of phthalonitrile, which possesses extremely strong chemical inertness and contains almost no easily hydrolyzable chemical bonds; the polydimethylsiloxane segments in the main chain endow the coating layer with excellent hydrophobicity, preventing the wetting and penetration of corrosive media; and the continuous Si-O-Si covalent bond network formed by the silane coupling agent and quartz sand eliminates interfacial gaps, cutting off the penetration path of corrosive media. In contrast, the phenolic resin of Comparative Example 1 contains a large number of easily hydrolyzable groups, resulting in a severe decline in performance after corrosion; although the resin body of Comparative Example 2 has good corrosion resistance, the coating cracks, leading to media penetration; the interfacial gaps in Comparative Example 3 become rapid channels for corrosive media; Comparative Example 4 lacks the hydrophobic barrier of long-chain siloxanes; and even the tiny interfacial gaps in Comparative Example 5 lead to slow penetration of corrosive media.

[0048] Regarding interfacial bonding and high-temperature anti-adhesion performance, the coating layer of Example 2 bonded most firmly to the quartz sand, and showed no adhesion at high temperatures. This is because the solvent-based pre-hydrolysis process fully hydrolyzes the silane coupling agent to generate highly active silanol groups, which undergo condensation reactions with the silanol groups on the surface of the quartz sand, forming molecular-level covalent bonds, significantly improving the interfacial shear strength. Simultaneously, the phthalonitrile resin, after curing, has no significant glass transition temperature and maintains a rigid three-dimensional network structure at 260°C, without softening or melting. The phenolic resin in Comparative Example 1 completely softened and bonded at high temperatures, relying solely on physical adsorption, resulting in extremely low interfacial strength. Comparative Examples 2 and 3 lacked covalent interfaces, leading to higher wear loss rates. Comparative Example 4 showed good interfacial bonding, but the resin's brittleness caused it to easily shed debris during wear. The silane in Comparative Example 5 was not fully hydrolyzed, resulting in weaker interfacial bonding than in Example 2.

[0049] Regarding long-term conductivity, Example 2 exhibited the highest long-term conductivity retention rate. This is because the fracturing quartz sand in Example 2 maintained its structural integrity under high temperature, high pressure, and corrosive environments, with no particle breakage, no coating peeling, and no particle adhesion, thus preventing the generation of fine powder that clogs the crack pores. In contrast, Comparative Example 1 showed a large amount of particle adhesion and breakage under high temperature, completely clogging the pores; Comparative Example 2 showed coating cracking leading to particle breakage and fine powder generation; Comparative Example 3 showed coating peeling, generating a large amount of fine powder and causing the most severe blockage; Comparative Example 4 showed a small amount of coating cracking due to brittleness, generating a small amount of fine powder; and Comparative Example 5 also showed a certain amount of fine powder generation due to interface peeling, affecting conductivity.

[0050] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A high-temperature resistant, corrosion-resistant coated fracturing quartz sand, characterized in that, The composition includes the following components in parts by weight: quartz sand: 90-100 parts, modified phthalonitrile resin: 3-10 parts; The modified phthalonitrile resin is prepared as follows: (1) Under nitrogen protection, hydroxyl-terminated polydimethylsiloxane was added to N,N-dimethylformamide and stirred for 20-30 min. Potassium hydroxide was added, the temperature was raised to 80-85℃, and the reaction was kept at the temperature for 3-5 h. Then the temperature was cooled to 30-40℃, 4-amino-5-nitrophthalonitrile was added, the temperature was raised to 85-95℃, and the reaction was kept for 6-9 h. After the reaction was completed, the temperature was cooled to room temperature, toluene was added, and the mixture was stirred for 10-20 min. Then the mixture was poured into dilute hydrochloric acid solution to precipitate. The mixture was filtered, and the filter cake was washed once with deionized water and once with ethanol. After drying, phthalonitrile containing flexible silane segments was obtained. (2) Under nitrogen protection, phthalonitrile containing flexible silane segments was added to anhydrous 1,4-dioxane, heated to 30-40°C, and stirred until dissolved. Then, 3-glycidyl etheroxypropyltrimethoxysilane was added, heated to 40-60°C, and stirred for 1-3 hours. After the reaction was completed, the reaction solution was poured into 3-10 times the volume of n-hexane to precipitate. The supernatant was poured off, and the precipitate was washed with n-hexane 3-4 times. After drying, modified phthalonitrile resin was obtained.

2. The high-temperature resistant and corrosion-resistant coated fracturing quartz sand according to claim 1, characterized in that, The number average molecular weight of the hydroxyl-terminated polydimethylsiloxane in (1) is 1500-2000.

3. The high-temperature resistant and corrosion-resistant coated fracturing quartz sand according to claim 1, characterized in that, In (1), the hydroxyl-terminated polydimethylsiloxane, potassium hydroxide and 4-amino-5-nitrophthalonitrile are in a molar ratio of 1:2.5-4:

2.

4. The high-temperature resistant and corrosion-resistant coated fracturing quartz sand according to claim 1, characterized in that, In (1), the hydroxyl-terminated polydimethylsiloxane, N,N-dimethylformamide, toluene and dilute hydrochloric acid solution are in a weight ratio of 1:2-3:0.5-1:10-20.

5. The high-temperature resistant and corrosion-resistant coated fracturing quartz sand according to claim 1, characterized in that, The concentration of the dilute hydrochloric acid solution in (1) is 3-10 wt%.

6. The high-temperature resistant and corrosion-resistant coated fracturing quartz sand according to claim 1, characterized in that, The (2) contains phthalonitrile with flexible silane segments and 3-glycidyl etheroxypropyltrimethoxysilane in a molar ratio of 1:2-2.

2.

7. The high-temperature resistant and corrosion-resistant coated fracturing quartz sand according to claim 1, characterized in that, In (2), the phthalonitrile containing flexible silane segments and anhydrous 1,4-dioxane are in a weight ratio of 1:5-10.

8. The method for preparing high-temperature resistant and corrosion-resistant coated fracturing quartz sand according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Add the modified phthalonitrile resin to acetone, stir until completely dissolved, add deionized water, adjust the pH to 4.5-5.0 with glacial acetic acid, stir evenly, and let stand at room temperature for 40-50 minutes to obtain a pre-hydrolyzed modified phthalonitrile resin solution. S2. Wash the quartz sand with deionized water until the conductivity is <10μS / cm, and dry it to obtain pretreated quartz sand; S3. Add the pretreated quartz sand to the coating machine, and spray the pre-hydrolyzed modified phthalonitrile resin solution through atomization in 8-12 minutes while stirring. After spraying, continue stirring for 10-20 minutes. Then, while stirring, raise the temperature to 75-85℃ and hold for 15-25 minutes, and then raise the temperature to 115-125℃ and hold for 25-35 minutes to complete the pre-condensation. S4. After pre-condensation, heat the sand to 180-190℃ at a rate of 2-5℃ / min and hold for 1 hour. Then heat the sand to 210-220℃ and hold for 1 hour. Finally, heat the sand to 240-260℃ and hold for 2 hours to obtain high-temperature resistant and corrosion-resistant coated fracturing quartz sand.

9. The method for preparing high-temperature resistant and corrosion-resistant coated fracturing quartz sand according to claim 8, characterized in that, In S1, the modified phthalonitrile resin, acetone, and deionized water are in a weight ratio of 1:3-6:0.1-0.2.